LymphMutSig - Wan, Hui (SciLifeLab Serve, 2026)
LymphMutSig is an interactive platform that provides a comprehensive atlas of mutational signatures in B-cell cancers and enables user-driven mutational signature analysis of B-cell cancer genomic data.